Beyond the Scope of Philosophy and Kabbalah - Ṿays, Tsaḥi (Religions, 2021)
The turn of the thirteenth century is a formative period for the historiography of medieval Jewish thought. These years saw the dissemination of the Hebrew translations of the Maimonidean corpus, alongside the simultaneous appearance of the first Kabbalistic treatises, in the same geographical regions. This concurrent appearance led scholars to examine Jewish theological discourse mainly via two juxtaposed categories: “Philosophy” and “Kabbalah”. In this paper, I will return to that formative moment in order to demonstrate that exploring Jewish history of ideas beyond the scope of these categories could be very advantageous in improving our understanding of both categories and the Jewish theological inner-dynamics in this period as a whole. I will draw attention to a contemporary theological attitude, which is neither Kabbalistic nor philosophical, which I will define as a medieval form of Jewish binitarianism. My argument in this paper will be composed of two parts—first, outlining the nature of this medieval Jewish theological trend, and second, showing how a precise definition of this belief within its context alters crucial notions and understandings in the common scholarly historiography of medieval Jewish thought.